Epidemiological modelling for the control of highly pathogenic avian influenza H5N1 (HPAI H5N1) in Egypt and Nigeria - Fasina, Folorunso Oludayo (2026)
Thesis (PhD (Epidemiology))--University of Pretoria, 2017.